Association of Sociodemographic Variables and Healthy Habits with Body and Visceral Fat Values in Spanish Workers - María Gordito Soler; Ángel Arturo López-González; Pedro Juan Tárraga López; Emilio Martínez-Almoyna Rifá; Cristina Martorell Sánchez; María Teófila Vicente-Herrero; Hernan Paublini; José Ignacio Ramírez-Manent (Medicina)
Background and Objectives: The accumulation of fat in the body, especially visceral fat, is associated with various cardiometabolic conditions such as diabetes mellitus and fatty liver. The reasons for the accumulation of this fat are diverse. Some studies, also in the working population, have shown a clear association between sociodemographic variables and health habits with scales that assess overweight and obesity. This study aims to determine how certain sociodemographic variables, such as age, gender, and socioeconomic level, as well as certain healthy habits like physical activity and tobacco consumption, affect the levels of body and visceral fat. Materials and Methods: We conducted a descriptive and cross-sectional study involving 8590 Spanish workers. The percentage of body and visceral fat was measured using a bioimpedance analysis with a Tanita DC 430MA device. Results: Both the average values and the prevalence of elevated body and visceral fat increase with age and decrease with social class and lower levels of physical activity. These values are higher in smokers. A multivariate analysis shows that the variables most influential in increasing the risk of high levels of both body and visceral fat are age and low levels of physical activity. Conclusions: The profile of a person at high risk of having elevated body and visceral fat levels is an older male with a low socioeconomic status who smokes and leads a sedentary lifestyle.